Suppression of SlMBP15 Inhibits Plant Vegetative Growth and Delays Fruit Ripening in Tomato - Yin, Wencheng; Yu, Xiaohui; Chen, Guoping; Tang, Boyan; Wang, Yunshu; Liao, Changguang; Zhang, Yanjie; Hu, Zongli (Frontiers in Plant Science, 2018)
MADS-box genes have been proved to participate in a number of processes in tomato development especially in fruit ripening. In this study, we reported a novel MADS-box gene, SlMBP15, which is implicated in fruit ripening. According to statistics, the ripening time of SlMBP15-silenced tomato delayed 2 to 4 days compared with the wild-type. The accumulation of carotenoid and biosynthesis of ethylene in fruits were decreased in SlMBP15-silenced tomato. Genes related to carotenoid and ethylene biosynthesis were repressed remarkably. SlMBP15 can interact with RIN, a MADS-box regulator affecting the carotenoid accumulation and ethylene biosynthesis in tomato. In addition, SlMBP15-silenced tomato generated dark green leaves and the plant height was reduced. The gibberellin (GA) content of transgenic plants were lower than wild-type and GA biosynthesis genes were repressed. These results demonstrated that SlMBP15 not only positively regulated tomato fruit ripening but also affected the morphogenesis of the vegetative organs.